Investigating the Presence of Falsified and Poor-Quality Fixed-Dose Combination Artemether-Lumefantrine Pharmaceutical Dosage Forms in Kumasi, Ghana - Simon Nyarko; Kwabena Ofori-Kwakye; Raphael Johnson; Noble Kuntworbe; Denis Dekugmen Yar (Advances in Pharmacological and Pharmaceutical Sciences)
Artemether-lumefantrine (AL) is a highly effective and commonly used Artemisinin-based Combination Therapy (ACT) for treating uncomplicated malaria caused by Plasmodium falciparum, including drug-resistant strains. However, ineffective regulatory systems in resource-limited settings can lead to the infiltration of poor-quality and counterfeit antimalarial medicines into the pharmaceutical supply chain, causing treatment failures, prolonged illness, and disease progression. The objective of the study was to assess the quality of selected brands of fixed-dose combination (FDC) AL tablets and suspensions marketed in Kumasi, Ghana. A total of fourteen brands of FDC AL medicines, comprising eight tablets and six suspensions were purchased from various retail pharmacy outlets in Kumasi, Ghana. All samples were subjected to thorough visual inspection as a quick means of checking quality through meticulous observation of the packaging or dosage form. The quality parameters of the tablets were determined using uniformity of weight, hardness, friability, and disintegration tests. Suspensions were assessed based on pH and compared with the British Pharmacopeia (BP) standard. The samples were then analyzed for drug content (assay) using reverse-phase high-performance liquid chromatography (RP-HPLC). All the tablet samples conformed to BP specification limits for uniformity of weight (deviation of less than ± 5%), hardness (4.0–10 kg/mm2), friability (<1%), and disintegration time (<15 minutes). The active pharmaceutical ingredients’ quantitative assay demonstrated that all the tablets met the BP specifications (90–110%). The results of the pH studies showed that out of the six brands of suspension investigated, five (83.3%) were compliant with the official specification for pH, while one (16.7%) failed the requirement. Unlike the tablet brands, drug content analysis of the six suspensions showed that two (33.3%) were substandard. The artemether and lumefantrine contents in these failed suspensions were variable (artemether: 81.31%–116.76%; lumefantrine: 80.35%–99.71%). The study results indicate that most of the tested products met the required quality standards, demonstrating satisfactory drug content and other quality specifications. The presence of substandard drugs underscores the necessity for robust pharmacovigilance and surveillance systems to eliminate counterfeit and substandard drugs from the Ghanaian market.